Assessing the effects of weekly preweaning health scores on dairy calf mortality and productivity parameters: cohort study. (19th August 2017) - Mahendran, Sophie Anne; Booth, Richard; Beekhuis, Lies; Manning, Al; Blackmore, Tania; Vanhoudt, Arne; Bell, Nick
Abstract : A longitudinal cohort study was conducted to follow the health of 787 calves from one UK dairy farm over a two‐and‐a‐half‐year period. Weekly health scores were gathered using a modified version of the Wisconsin Calf Scoring system (which did not record ear position) until calves were eight weeks of age, combined with data on colostral passive transfer, mortality, age at first conception and 305‐day milk yield. High morbidity levels were detected, with 87 per cent of calves experiencing at least one clinically significant event (diarrhoea, pyrexia, pneumonia, nasal or ocular discharge, navel ill or joint ill). High rectal temperature, diarrhoea and a cough were the most prevalent findings. The effect of total protein levels was significantly associated with the development of pyrexia as a preweaning calf (P<0.01), but no other clinical health scores. The majority of moribund calves had just one clinically severe clinical sign detected at each of the weekly recordings. The overall mortality rate was 21.5 per cent up to 14 months of age, with 12.7 per cent of calves dying during the preweaning period. However, most calves that died were not recorded as having experienced a severe clinical sign in the time between birth and death, indicating a limitation in weekly calf scoring in detecting acute disease leading to death. Therefore, more frequent calf scoring or use of technology for continuous calf monitoring on farms is required to reduce mortality on farms with high disease incidence rates.